Comparison of shear bond strength between direct and indirect bonding methods in vitro - Samera Kiran; Lubna Batool Mahpara; Asif Nazir; Arfan ul Haq (Medical Journal of South Punjab, 2024)
Objective: to compare the shear bond strength of orthodontic brackets bonded using direct bonding technique versus indirect bonding technique. Methods: This study was conducted at the Department of Orthodontics of Nishtar Institute of Dentistry, Multan in collaboration with PCSIR Laboratories, Lahore. In this experimental in vitro study, there were 600 extracted human premolar teeth which were mounted on the fifty cold-cure acrylic blocks having twelve teeth each and each tooth was bonded separately. The sample was randomly divided into two groups including 300 teeth i.e. twenty-five blocks in each of the group. Group A included the teeth with indirectly bonded brackets and Group B comprised of those with directly bonded brackets. Results:The average shear bond strength of all the 600 teeth was 14.70±4.62 N/mm2. Directly bonded specimens showed higher mean shear bond strength (15.62±4.74 N/mm2) than indirectly bonded specimens (13.77±4.31 N/mm2). Conclusion: There was makeable difference present between mean shear bond strength of both groups. Brackets bonded with direct bonding technique had greater shear bond strength than brackets bonded with indirect bonding method.